Index of Adaptability to Green Economy:: An Evaluation of the Sugar Cane Production Sector at the Micro- Region of Ribeirão Preto / São Paulo State, Brazil - Bezerra, Karine Rocha Aguiar; Martins, Minella Alves; Velloso, Maria Francisca Azeredo; Furtado, Michelle Andrade (Sustainability in Debate, 2014)
The Green Economy (GE) is an emerging issue in the context of scientific and political wide discussions. Its main challenge is to turn economic activities into sustainable activities. The production chain of cane sugar involves social, economic and environmental aspects controversial. Thus, the aim of this study was to evaluate the adjustment with the principles of EV of the culture in question in the microregion of Ribeirão Preto (SP). Therefore, we developed the Index Adaptability to the Green Economy (IAGE), which consists of Partial Indexes (Economic Impact ”“ PIEI; Social Impact ”“ PISI, and Environmental Impact ”“ PIEI). The construction of such indexes was based on variables provided by agencies such as IBGE, SUS, SEADE and CANASAT/INPE. In general terms, the microrregion in study presented an improvement in IAGE in a decade (2000 and 2010). We also demonstrate that the social and environmental partial indexes were the lowest values; priority areas for future investments.